Galenics and their promotion in pharmacies - Mavridou, Maria Myrto; Goula, Maria2 (Health & Research Journal, 2017)
In the present article galenical formulations are defined and some of their characteristics are analyzed in order to present their significance even in our days and age. Prescription forms, symbols and abbreviations as well as general information that are widely accepted by international scientific community are provided. General information about them are also provided. Medical specialties that propose the use of galenics as well as limitations concerning their use are mentioned. Furthermore, their use from special patient populations is discussed. The procedure that must be followed to produce galenics as well as the expiration and discard dates, the listing of ingredients on the package and its costing are necessary elements for their consuming, reproduction or replacement. Despite the skepticism with which galenics are dealt with by organizations that are relevant with quality control of medications, their uses not only in dermatological conditions and cosmetology but also in pediatrics, gynecology and trauma are well known from the past. Moreover, ways of promotion for cosmetic pharmaceutical products and researches on consumers’ preferences are cited. Our aim is to present the timeless value and usefulness of galenics in aesthetics and dermatology, and to highlight the contribution of proper promotion of these products in pharmacies